2020
DOI: 10.1097/ta.0000000000002912
|View full text |Cite
|
Sign up to set email alerts
|

Association of timing of initiation of pharmacologic venous thromboembolism prophylaxis with outcomes in trauma patients

Abstract: BACKGROUND Patients are at a high risk for developing venous thromboembolism (VTE) following traumatic injury. We examined the relationship between timing of initiation of pharmacologic prophylaxis with VTE complications. METHODS Trauma quality collaborative data from 34 American College of Surgeons Committee on Trauma–verified levels I and II trauma centers were analyzed. Patients were excluded if they were on anticoagulant therapy at the time of injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 33 publications
1
47
0
Order By: Relevance
“…Low molecular weight heparin (LMWH) has been shown to be superior to unfractionated heparin (UFH) in this cohort, with improved survival and fewer thromboembolic complications 286 . Owing to patient immobility and the hypercoagulable state, thromboprophylaxis is administered as soon as possible after the bleeding risk has subsided, and individual patient factors must guide the choice of UFH or LMWH 287,288 .…”
Section: Special Considerationsmentioning
confidence: 99%
“…Low molecular weight heparin (LMWH) has been shown to be superior to unfractionated heparin (UFH) in this cohort, with improved survival and fewer thromboembolic complications 286 . Owing to patient immobility and the hypercoagulable state, thromboprophylaxis is administered as soon as possible after the bleeding risk has subsided, and individual patient factors must guide the choice of UFH or LMWH 287,288 .…”
Section: Special Considerationsmentioning
confidence: 99%
“…It is important to note that there is evidence that an even earlier VTEp (<24 h) may be safe and more effective. [25][26][27] In the present study, 626 patients (8.5%) received VTEp before 24 h. This small proportion precludes any meaningful further analysis. Future studies should investigate if an even earlier VTEp may be safe and more effective, especially in patients with TBI.…”
Section: Discussionmentioning
confidence: 74%
“…In particular, the risk and benefit determination of pharmacologic thromboprophylaxis is dependent predominantly on definitions of VTE events and bleeding outcomes (Supplement, http://links.lww.com/SLA/D373). However, we demonstrate in this review that the definitions for these outcomes are frequently either not reported due to limitations of large administrative datasets, [28][29][30][31][32][33][34] subjectively determined without a reported clinical rationale 15,16,27 or inconsistent across studies. 15,16,26,27,33 For example, the use of screening ultrasounds will increase the DVT detection rate and often identify distal DVTs that are prognostically less significant than proximal DVTs.…”
Section: Discussionmentioning
confidence: 99%